Differences in clinical characteristics for the determination of adenomyosis coexisting with leiomyomas. Issue 3 (10th December 2015) - Ates, Seda; Ozcan, Pinar; Aydin, Serdar; Karaca, Nilay
Abstract: Aim: The objective of the analysis was to determine the characteristics that distinguish women with adenomyosis and leiomyomas from those with leiomyoma only from a sample who underwent hysterectomy for benign uterine diseases. Methods: This retrospective study was based on the analysis of medical records of 75 women with both adenomyosis and uterine leiomyomas and 218 women with leiomyomas only, diagnosed by histologic analysis of uterine specimens. Results: Results of multivariate logistic regression analyses showed that women with both adenomyosis and leiomyomas had a higher gravity (odds ratio [OR] 1.16, 95% confidence interval [CI] 1.01–1.33) and more frequent pelvic pain (OR 0.38, 95% CI 0.21–0.7) compared with women with leiomyomas only. Postmenopausal bleeding was commonly reported in women with adenomyosis and leiomyomas. No significant difference was observed between the two groups in terms of menorrhagia and metrorrhagia and the preoperative diagnosis of prolapse. Conclusions: The presence of concomitant adenomyosis may cause different clinical symptomatology.